Optimalization of Management System of Municipal Solid Waste Transportation (Case Study: Jakarta, Indonesia) - Ulhasanah, Nova; Ulhaq, Muhamad Hisyam Dhiya; Zahra, Nurulbaiti Listyendah (Journal of Sustainable Infrastructure, 2024)
West Jakarta has the farthest distance for the waste transportation process compared to other municipalities in DKI Jakarta. The number of population and garbage which always increases every year can make the West Jakarta area experience new problems with the waste transportation system. In existing conditions, there are 68 out of 195 trucks in 174 temporary trash shelter that do not have a volume of waste that can immediately fill containers in 1 day of garbage collection. The trucks have to wait for further collection until the truck containers are filled. In addition, there are 31 trucks which transports waste in temporary waste shelter with a generated amount that exceeds the capacity of the truck. This can cause the waste to settle at the temporary trash shelter or the truck will carry more waste than it’s capacity. Therefore, the goal to be achieved in this design is to optimizing the waste transportation system in West Jakarta with SCS from a technical and economic point of view. After evaluating the existing conditions and analyzing the alternative choices made, it was found that the system can be optimized using the Hauled Container System (HCS) and the Stationary Container System (SCS) with 1 and 2 transportation rit / day. The number of trucks could be reduced from 195 to 73, with 70 trucks doing 2 rit / day and 3 trucks doing 1 rit / day. The number of drivers can be reduced from 195 to 143 drivers, with each driver only working for 1 rit. There was a decrease in the cost of diesel fuel / month from Rp873,158,589 to Rp853,612,500 and could reduce the driver's wages from Rp711,366,825 to Rp521,669,005 each month. The total transportation cost for diesel fuel and employee wages in a month is Rp1,375,281,505 or Rp209,243,909 cheaper than the existing conditions.